THE USE OF MNEMONIC METHODS IN CHEMICAL EDUCATION - Kuchkarov, Mexriddin (Theoretical and experimental chemistry and modern problems of chemical technology, 2023)
This article analytically describes the possibilities of forming the cognitive abilities of students. It focused on the use of mnemonics methods in chemical education. The use of mnemonics techniques in the assimilation of information is justified, develops the cognitive abilities of students.